2020
DOI: 10.1002/jctb.6341
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of anti‐fouling novel cellulose/graphene oxide (GO) nanosheets (NS) microfiltration membranes for seawater desalination applications

Abstract: BACKGROUND Reverse osmosis (RO) is becoming the predominant technology for the future of desalinated of seawater. Nonetheless, operational challenges such as membrane biofouling in RO desalination plants result in membrane deterioration and high energy costs. In this regard, pre‐treatment technologies, such as microfiltration (MF) membranes, are proven to reduce the impact of membrane biofouling in RO systems. Hence, surface modifications of commercial cellulose MF membranes with graphene oxide nanosheets (GON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 52 publications
(113 reference statements)
0
12
0
Order By: Relevance
“…Membrane fouling/clogging is a catastrophic phenomenon that restricts the performance of ceramic membranes during oily wastewater treatment filtration. 11 In this regard, surface wettability has been reported to have a significant role in the improvement of membrane efficiency. 1,2,12,13 Superhydrophobic-superoleophilic materials are preferred in the absorption of low surface tension oil molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane fouling/clogging is a catastrophic phenomenon that restricts the performance of ceramic membranes during oily wastewater treatment filtration. 11 In this regard, surface wettability has been reported to have a significant role in the improvement of membrane efficiency. 1,2,12,13 Superhydrophobic-superoleophilic materials are preferred in the absorption of low surface tension oil molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, ceramic membrane application has its limitations. Membrane fouling/clogging is a catastrophic phenomenon that restricts the performance of ceramic membranes during oily wastewater treatment filtration 11 . In this regard, surface wettability has been reported to have a significant role in the improvement of membrane efficiency 1,2,12,13 …”
Section: Introductionmentioning
confidence: 99%
“…1 Since cellulose acetate, as a kind of biodegradable polymeric material, is widely available with low cost, superior resistance to chlorine, and renewability, they are valuable choices for the synthesis of FO membranes. [12][13][14][15] Recently, nanocomposite membranes have been considered to be promising advanced membranes for seawater desalination because of improvements in their performance, which were induced by the incorporation of NPs into membrane structures. 16 Various research groups have tried to improve the membrane substrate functions using NPs, such as zeolites, silver, silica, titanium dioxide (TiO 2 ), graphene oxide (GO), and carbon nanotubes (CNTs).…”
Section: Introductionmentioning
confidence: 99%
“…So far, various types of polymeric materials have been used to fabricate FO membranes, such as polysulfone (PSF), polyethersulfone (PES), and their sulfonated materials 1 . Since cellulose acetate, as a kind of biodegradable polymeric material, is widely available with low cost, superior resistance to chlorine, and renewability, they are valuable choices for the synthesis of FO membranes 12–15 . Recently, nanocomposite membranes have been considered to be promising advanced membranes for seawater desalination because of improvements in their performance, which were induced by the incorporation of NPs into membrane structures 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Industrial operations involving processing of complex compounds such as proteins and microorganisms tend to face severe biofouling. Biological processing of materials, food processing industries and pharmaceutical industries need the latest hybrid membranes to overcome the problem of biofouling 1–4 . Foulants in industrial wastes or found in natural substances not only interact physically with membrane surfaces but can also lead to deterioration of the chemical structure of membranes permanently 5–10 .…”
Section: Introductionmentioning
confidence: 99%